2009
DOI: 10.1590/s1516-35982009000600025
|View full text |Cite
|
Sign up to set email alerts
|

Análise da sensibilidade da metodologia dos centros de custos mediante a introdução de tecnologias em um sistema de produção de cria

Abstract: RESUMO -Um modelo de simulação bioeconômico foi desenvolvido em um sistema de produção tradicional em pecuária de cria (SPT) para a aplicação da metodologia dos centros de custos com o objetivo de avaliar sua sensibilidade mediante a introdução de tecnologias de desmame precoce em vacas primíparas (SDP), campo melhorado para vacas primíparas e metade do lote das vacas secundíparas (SCM) e suplementação protéica para novilhas de reposição (SSP) destinadas a aumentar a taxa de prenhez neste sistema (SPT). As inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
0
4
0
12
Order By: Relevance
“…Oiagen et al (22) found that operational costs increased with the introduction of technologies, indicating that, when the system is intensified significant increases occurs in variable costs, especially in feed. Missio et al (1) cite that the model of traditional system has proven economically inefficient, where the reduction in age of slaughter becomes a viable alternative, since it provides higher turnover from invested capital.…”
Section: Resultsmentioning
confidence: 99%
“…Oiagen et al (22) found that operational costs increased with the introduction of technologies, indicating that, when the system is intensified significant increases occurs in variable costs, especially in feed. Missio et al (1) cite that the model of traditional system has proven economically inefficient, where the reduction in age of slaughter becomes a viable alternative, since it provides higher turnover from invested capital.…”
Section: Resultsmentioning
confidence: 99%
“…São necessários cuidados na interpretação analisando a metodologia de resultados experimentais quando estes envolvam produtividade e eficiência de raças e sistemas de produção de gado de cria (BARCELLOS; FRIES, 1996;OAIGEN et al, 2009). …”
Section: Resultsunclassified
“…In addition, production systems that apply technologies and manage them using production and economic indexes are more bioeconomically efficient (Oaigen et al, 2009). Therefore, the lack of production and financial control compromises the efficient use and management of the available technologies by the farmers in the LEL cluster.…”
Section: Discussionmentioning
confidence: 99%